Hoe zou een publieke datadonatiepraktijk ten behoeve van gezondheid en welzijn eruit kunnen zien? - Rijshouwer, Emiel; Butot, Vivien; Al-Hassany, Linda; Leclercq, Els; Roeters van Lennep, Jeanine; Maassen van den Brink, Antoinette (TU Delft Open, 2023)
datadonatie;convergence;gezondheid;welzijn